Social sustainability and the argan boom as green development in Morocco. (December 2020) - Perry, Wendy
Highlights: Morocco links reforestation and women's empowerment in the booming argan industry. As global demand for argan oil rises, so do profits at the top of the value chain. Impact evaluation shows uneven, meager rewards for women's skilled manual labor. The centralized, unregulated market-driven argan sector exposes locals to risks. Socially responsible measures at the international, national, and local levels can promote balanced sustainability. Abstract: Morocco markets argan oil as a fair-traded, organic health and beauty elixir that women extract in an ancient forest protected internationally to clean the world's air. Since the 1990s, the kingdom has partnered with global governance organizations and foreign investors to develop the argan forest as a coveted natural resource, designated a UNESCO Biosphere Reserve in 1998. Large-scale investments in reforestation and "arganiculture" propose to mitigate carbon emissions, alleviate poverty, and empower women workers at proliferating state-subsidized argan oil cooperatives in the export-oriented commodity value chain. This impact evaluation of the booming argan enterprise weighs the social benefits and costs of a transnational push that prioritizes economic growth over social sustainability. Empirical data from 829 surveys with local residents depict an unregulated, informal commercial sector at odds with the inclusive neoliberal development narrative on the whole. Results show rural women and their communities exposed to risks in a centralized, market-driven extractivist industry geared toward consumers. The top-down argan boom has triggered new legislation and innovations in science and technology that have shifted control of the land, agroforestry practices, and oil extraction process from local producers to the state. Women and the rural poor have thus been divested of their patrimony and marginally sustained as manual labor rather than effectively empowered. Moving forward, rebalancing economic, environmental, and social sustainability priorities will require initiatives informed by empowerment indicators, revised regulatory policies, diversified investment strategies, and commitment to assuring compliance, transparency, and impartial assessment of benefits and costs to women workers.